The Arts & Leadership: Now That We Can Do Anything, What Will We Do? (LEARNing Landscapes, 2008)
Given the dramatic changes taking place in society, the economy, and technology, 21st century organizations need to engage in new, more spontaneous, and more innovative ways of managing. I investigate why an increasing number of companies are including artists and artistic processes in their approaches to strategic and day-to-day management and leadership.
Keywords: art; management; change; 21st century; leadership; economy